Crystal structure of (Z)-3-((tert-butylamino) methylene)-2-(2-hydroxynaphthalen-1-yl) chroman-4-one, C24H23NO3 - Liu Tianhao; Lv Menglan (Zeitschrift für Kristallographie - New Crystal Structures)
C24H23NO3, orthorhombic, Pna21, a = 8.2490(11) Å, b = 15.886(2) Å, c = 16.218(2) Å, β = 99.465(2)°, Z = 4, V = 2096.4(5) Å3, Rgt(F) = 0.0545, wRref(F2) = 0.1688, T = 273 K.